0650 Normative EMG Values and Isolated Rapid Eye Movement Sleep Without Atonia Frequency in Adults without REM Sleep Behavior Disorder. (12th April 2019) - Feemster, John C; Jung, Jessica; Timm, Paul C; Westerland, Sarah M; Gossard, Thomas; Teigen, Luke; Cattaneo, Elena; Imlach, Charlotte; McCarter, Stuart J; Smith, Kevin L; Boeve, Brad F; Silber, Michael H; et al.
Abstract: Introduction: Normative REM sleep without atonia (RSWA) values remain unclear. In adults without REM sleep behavior disorder (RBD), older age and male sex are associated with greater RSWA. Isolated elevated RSWA has also been reported as a possible prodromal synucleinopathy parallel to, yet distinct from, REM sleep behavior disorder (RBD). We aimed to describe normative RSWA and characterize isolated elevated RSWA frequency in adult patients without RBD seen in our clinical sleep medicine practice. Methods: We visually quantified phasic, "any", and tonic RSWA in the submentalis (SM) and anterior tibialis (AT) muscles, and the automated Ferri REM Atonia Index (RAI) during polysomnography in adults without RBD aged 18-88 years old. RSWA percentiles were calculated across sex and age deciles, and RSWA in older (≥ 65) vs. younger (<65 years old) men and women was compared. Isolated RSWA (exceeding previously determined diagnostic RBD cut-offs, or above 95 th percentile) frequency was also determined. Results: Overall 95 th percentile RSWA percentages were: SM phasic, any, tonic=8.6%, 9.1%, 0.99%; AT phasic and "any"=17.0%; combined SM/AT phasic, "any"=22.3%, 25.5%; and RAI=0.85. Most phasic RSWA burst durations were ≤ 1.0 second (85 th percentiles: SM 1.07, AT 0.86 seconds). Older men had significantly higher AT RSWA than older women and younger patients (all p<0.04). Twenty-nine (25%, 18 men) had RSWA exceeding the cohort 95 th percentile, while 17 (14%, 12 men) fulfilled diagnostic cut-offs for phasic or automated RBD RSWA thresholds. Conclusion: RSWA levels are highest in older men, mirroring the demographic characteristics of RBD, possibly suggesting altered REM sleep atonia control in older men. These data establish normative adult RSWA values and thresholds for determination of isolated RSWA elevation, potentially aiding RBD diagnosis and discussions concerning incidental RSWA in clinical sleep medicine practice. Support (If Any): Mayo Clinic CCaTS, and Mayo Clinic Alzheimer's Disease Research Center